Rudin-type Dowker spaces - Kojman, Menachem (Topology Proceedings, 2025)
A construction scheme of topological spaces, which generalizes M. E. Rudin’s construction of a Dowker space in ZFC, is given, and is shown to produce a proper class of Dowker spaces. A proper subclass of this class of spaces are provably collectionwise normal Dowker in ZFC alone. The theory ZFC + SSH, where SSH is Shelah’s Strong Hypothesis, proves that the whole class consists of collectionwise normal Dowker spaces. Whether all members of this class are Dowker in ZFC is still open.